Analisis Balik Kestabilan Lereng Dengan Menggunakan Metode Bishop yang disederhanakan Pada Front II Existing Tambang Quarry PT. Semen Padang, Sumatera Barat - Riri Metriani; Yoszi Mingsi Anaperta; Tri Gamela Saldy (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. In 2018 the slope in the exisiting front II area will experience rocky weathering where the landslide that has been identified is in the form of an avalanche. The method used in this research is the bishop method and the hoek & bray method. As a result of the study, the following conclusions are made. First Results FK values are based on parameter values of physical-mechanical properties with slope geometry. With a safety factor value in dry conditions of 1.947, in the half-saturated condition of 1.793 and in the saturation condition of 1,514 . second landslides that occurred were bow avalanches. The three results of the analysis behind the landslide are cohesion value of 124 kN / m2 and shear angle in 24 °. Third during dry conditions with fk by using methods bishop 1.471 single slope and fk overall slope 1,339 by using Hoek and Bray 2,34. with saturated conditions fk value using the bishop 1.416 single slope and fk overall slope 1,337 and the hoek and bray method 2,34. in a half-saturated condition fk value using the bishop method fk value 1,391 single slope and fk overall slope 1,398 and by using the hoek and bray method fk value 2,34.